Analisis Pengaruh Jakarta Islamic Index, Nilai Tukar Rupiah Dan Neraca Perdagangan Terhadap Ekspor Industri Pada Tahun 2020-2024 - Muflihah, Inaayatul; Hermawati, Syabila Dwi; Zahra, Andin; Mahfud, Alvin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze the influence of the Jakarta Islamic Index (JII), the exchange rate of the rupiah, and the trade balance on industrial exports in Indonesia during the period of 20202024. These three variables were chosen because they are considered to have a close macroeconomic relationship with the export performance of the industrial sector. To identify both short-term and long-term relationships among the variables, this study uses the Vector Error Correction Model (VECM). The data used are monthly time series data from 2020 to 2024 obtained from official sources such as the Badan Pusat Statistik (BPS), Kementerian Perdaganagan and Bank Indonesia. The results show that in the short term, the exchange rate and trade balance significantly affect industrial exports, while the JII does not show a significant effect. However, in the long term, all three variables have a significant relationship with industrial exports, with varying directions of the relationship. The error correction mechanism indicates that the system has the ability to return to long-term equilibrium in the event of deviations. These findings highlight the importance of exchange rate stability and strengthening the trade balance in supporting the performance of Indonesia's industrial exports. Additionally, the development of the sharia capital market through JII also needs to be considered in the context of sustainable industrial development.